Phytoplankton abundance and the relation with water quality around fish cage in the Koto Panjang Reservoir Tanjung Alai Village, Kampar, Riau Province - Muzakki, M. Hafiz; Fajri, Nur El; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from October to Desember 2014 in the Koto Panjang Reservoir Tanjung Alai Village and aims to understand the relation phytoplankton abundance and water quality around the fish cage aquaculture activities. There were 3 stations and 3 sampling points in each station. Water samples were taken 3 times, once/ week. Water quality parameters measured were water temperature, brigthness, DO, pH, nitrate and phospate. Phytoplankton were identified based on Yunfang (1995) and Sachlan (1980). Results shown that there were 4 classes present (3.067–6.275 cell/L), namely Chlorophyceae (12 genus), Bacillariophyceae (8 genus), Cyanophyceae (7 genus), and Xanthophyceae (2 genus). Water quality parameters are as follows temperature: 29.0–30.0 0C, brigthness: 72.7–137.9 cm, DO : 4.7–5. 3 mg/L, pH : 4.7–5.3, nitrate: 0.026–0.030 mg/L, and phosphate : 0.3–0.4 mg/L. It can be concluded that the phytoplankton abundance will be increased as the fish cages amount.Keyword: Phytoplankton Abundance, Koto Panjang Reservoir, Tanjung Alai Village